Ergonomic assessment of musculoskeletal symptoms and associated risk factors among pineapple plantation workers - Nur Fazrina Mohamad, Salleh (2019)
Malaysia is on an attempt to become one of the largest producers of pineapples in Southeast Asia. As there are many new developed pineapple plantation areas, there are high job demands to work in this sector. Agricultural works is always associated with high demand, heavy and labor intensive works. Thus, plantation workers are constantly at risk for developing Work-Related Musculoskeletal Disorders. Pineapple plantation job activities start with planting, maintaining, manual weeding and harvesting. These job activities are known as quite repetitive, long time consuming and laborious in nature. In spite of various prolonged awkward postures, the workers also exposed to heavy manual work during harvesting activity. This study aims to identify the prevalence of musculoskeletal symptoms among workers of pineapple plantations; analyze the postural analysis assessment; and to test the postural scores in terms of its validity. Data collection was conducted in three different pineapple plantations in Pahang which took three months. A modified questionnaire adapted from Nordic Musculoskeletal Questionnaire was used during recognizing the prevalence of musculoskeletal symptoms among the workers. Dynamic activities of workers were recorded and by using stand still photos, two type of postural assessment; Ovako Working Posture Analysis System (OWAS) and Manual Handling Assessment Chart (MAC) were carried out. After that, the results were validated by using Surface Electromyography (sEMG) technique. The survey results showed that 62.1% of workers experienced lower back pain, followed by 58.2% of workers experienced pain on the waist and 33% of workers felt pain on their knees. OWAS identified three activities; planting (39.8%), manual weed (42.7%) and harvesting (60.2%) were categorized mainly in Action Category 3 which indicated distinctly harmful. Meanwhile, planting (17.5%) and manual weed (27.2%) also fell into Action Category 4 which indicated as extremely harmful. MAC assessment for lifting activity showed that 100% were in level 3 (risk level 13-20), signify that action required soon. On the other hand, carrying activity showed that 33.3% were in level 2 (risk level 5-12), signify that action required near future whereas 66.7% were in level 3 (risk level 13-20) which signify action required soon. The overall result from the study shows that pineapple plantation workers are highly exposed to ergonomic hazards risk factors such as awkward postures and heavy lifting. This study suggests that ergonomic intervention such as mechanization of tools and equipment should be implemented in order to eliminate poor postures and manual handling task. In case of incapability for any mechanization, adequate and effective training should be constantly provided. Therefore, workers can implement safe work practices.